Activation of oxidative stress, comorbidity and survival of end-stage renal disease patients treated with hemodialysis - I. Shifris; L. Korol; Е. Krasiuk; S. Dudar (Ukrainian Journal of Nephrology and Dialysis, 2021)
Abstract. The aim of the study was to analyze the characteristics of serum concentrations of oxidative stress (OS) markers depending on the quantitative assessment of comorbidity and taking into account the most informative indicators of OS, to prospectively assess changes in comorbid status, death rates and individual comorbid conditions in patients with end-stage renal disease (ESRD) treated with hemodialysis (HD).Methods. The cohort prospective open-label study included 156 patients with ESRD, treated with HD. The study was conducted in two stages. In the first – the structure and quantitative assessment of comorbid diseases, determination of serum concentrations of oxidative stress (OS) markers and their analysis depending on the comorbid status were studied. On the second – taking into account the defined threshold values (Cut-off) of the most informative markers of the OS, an assessment of changes in comorbid status, frequency of comorbid conditions and fatal events done. A modified polymorbidity index (MPI) was calculated to assess comorbid status. The concentration of OS serum markers was determined by spectrophotometric method. Statistical analysis was performed by using "MedCalc", version 19.3 (Ostend, Belgium).Results. Serum concentrations of all prooxidant markers were significantly higher and antioxidant markers were significantly lower in the HD patients with high comorbid status compared to those of patients with low comorbidity (p<0.0001). Correlation analysis between MIP and the studied OS markers showed that the largest correlation (rho=0.874) was established with the serum concentration of malondialdehyde (MDAs). During the observation period in the group of patients with a concentration of MDAs > 668.72 μmol/ml found a significant, compared with the group with a biomarker content ≤ 668.72 μmol/ml, an increase in the proportion of patients with chronic obstructive pulmonary disease (COPD) (by 81.84 % vs 28.48 %; p<0.0001), cardiovascular diseases (CVD) (by 56.0 % vs 36.4 %; p=0.019) and cerebrovascular (CEVD) diseases (by 73.33 % vs 30.42 %; p<0.0001). The proportion of patients with fractures in the group of patients with MDAs > 668.72 μmol/l increased fourfold (p=0.0140). The increase in MIP is 34.11 % vs 17.1 % (p<0.0001), five-year cumulative survival – 45.3 % vs 63.3 % (p=0.0312; HR – 2,1527, 95% CI: 1,2458 –3,7199), five-year CV survival – 61,6 % vs 80.8 % (p=0.0094; HR – 2.7955, 95% CI: 1.3664 – 5.7191) in groups with MDAs > 668.72 and ≤ 668.72 μmol/ml, respectively.Conclusions. In patients with ESRD, treated with HD, serum concentrations of MDAs > 668.72 μmol/l is a biochemical determinant of a significant increase, in the medium term, the number of comorbid conditions, deaths, fatal CV and CEVD events, the proportion of patients with COPD, fractures, CVD and CEVD, reduction of cumulative and CV survival.